Specialty selection satisfaction and regret among medical school postgraduates and faculty at King Abdulaziz University - Mashat, Muhammed A.; Aboalfaraj, Nawaf T.; Daghistani, Hussam; Eldeek, Basem S.; Ayuob, Nasra N.; Alshawa, Lana A. (International Journal of Research in Medical Sciences, 2017)
Background: In the field of medicine, specialty selection is a life-altering decision that plays a crucial role in career satisfaction, and in turn patient-care. This study explores the significant factors affecting specialty selection satisfaction and regret from the perspective of medical postgraduates and faculty in King Abdulaziz University (KAU). Methods: A cross sectional study was carried out on a sample of 172 medical school postgraduates and faculty working at KAU using self-administered questionnaire. Results: The majority of the participants were residents (51.7%), The analysis showed that 11% of the participants regret their choice of specialty. The results showed that the level of satisfaction increases as the academic degree of the participants increase. Among the significant factors affected specialty selection satisfaction and regret were; income (P = 0.003), long length of training (P = 0.027), vast options of sub-specialties (P = 0.001) and interesting and exciting field. Conclusion: These results identify the essential factors that have a potential impact on specialty satisfaction and regret among medical school postgraduates and faculty. This highlights the importance of career counseling for the proper specialty selection.